Research infrastructure, networks of science and regional development: The case of Oskarshamn - Folke Valfrid Snickars; Ulf Karlsson (REGION, 2017)
Final deposit of nuclear waste is a a global engineering challenge. The Swedish nuclear industry has spent more than thirty years in investigating the best sites and technologies for the final storage of nuclear waste. Universities have been involved as experts in this massive R&D activity. The result has been a well-documented body of knowledge for decision support. At the same time global research infrastructure networks have been developed. More than 140 PhD theses have been produced as one of the outputs. Eleven of these PhD holders are now full professors. Based on earlier work on research infrastructures Lund, Hamburg, and Kiruna, see for instance Snickars and Falck (2015), we have addressed the question of the role of a technical research infrastructure for the development of fields of engineering and natural science at the same time generating regional development. It has provided an opportunity to empirically study the use of research infrastructure in a specialized technology field. At the same time the study investigates a municipality's efforts to specialize in research without a university in the vicinity. Do networks of cooperation differ between research groups and research infrastructures? Can a region build its smart specialization on research infrastructure? Can research equipment once belonging to a company be transformed to a public research infrastructure asset? Our results indicate that research infrastructures as the ones in Oskarshamn are powerful creators of international research networks. It is possible although somewhat difficult in view of scattered systems for data provision to assess their academic and societal impacts. Engineering research has its own networks of university-industry and industry-university interaction where value is cogenerated dynamically. In the study we have come some way towards empirically analyzing the networks of research cooperation between industry and university using methods of infrastructure theory and network analysis.
Keywords: 330; Extenalities; Environment